Manajemen Program Pembelajaran Bahasa Arab dengan Metode Langsung (Direct Method) di Pondok Tahfidz Putri Darul Mubarok Curup (DMC) - Rahmad Arif Setiawan; Nuril Mufidah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study determines the management of teaching arabic language with direct method, this study uses qualitative descriptive with analysis method’s huberman and miles which is data display, data analysis, data reduction and conclusion. This study answering the question, those are; 1) How management of the arabic language learning program using the direct method (direct method) at the pondok tahfidz putri daarul mubarak curup (dmc)? 2) What are the supporting factors and inhibiting factors in the management of the Arabic language learning program using the direct method at the Pondok Tahfidz Putri Daarul Mubarak Curup (DMC)?. The results of this study include several things; 1) The implemented management of the arabic language learning program using the direct method (direct method) at the pondok tahfidz putri daarul mubarak curup (dmc) based on 4 management functions namely; a. Planning function: In planning Arabic learning the teacher prepares a Lesson Plan (RPP) which includes equipment or auxiliary media to facilitate the Arabic learning process, while also preparing a number of questions about material that has previously been taught to recall the lessons that have been taught, this can also improve students' cognitive abilities with the drill method used by the teacher when asking indirectly questions that are routinely given and continuously related to the lessons that have been taught, b. Organizing function: In the process of organizing learning the Arabic teacher at the tahfidz Putri Daarul Mubarok Curup Islamic boarding school organizes learning by managing the time when teaching, inviting students to ask questions, conducting questions and answers, determining activities and materials, paying attention to start and finish times of learning, the process of organizing learning These are arranged systematically to make it easier for teachers to carry out learning activities. c. Implementation function: The Arabic teacher at Pondok Tahfidz Putri Daarul Mubarok Curup carries out the function of implementing Arabic learning with the following stages: 1. Pre-instructional stage; The teacher greets the students by saying